2018
DOI: 10.1177/1687814018756103
|View full text |Cite
|
Sign up to set email alerts
|

A multi-agent scheduling problem for two identical parallel machines to minimize total tardiness time and makespan

Abstract: We study an agent-based scheduling problem of two identical parallel machines:. The machines and tasks are regarded as agents. A new multi-agent scheduling model is proposed to achieve the optimum from the two task agents, agent A and agent B. The objective is divided into two classes. The objectives of agent A and agent B are to minimize the total tardiness time and minimize the makespan, respectively. In this article, we research two identical parallel machines in which one job category can be processed by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…e literature studies other variants of the two-agent scheduling problem. However, they differ from the problem considered in this paper in terms of either objective function (Wan et al [21]; Mor and Mosheiov [22]) or machine settings (Mor and Mosheiov [23]; Lei [24]; Yu et al [25]). A literature survey by Li et al [26] and Yin et al [27] can be referred to find different variants of the two-agent scheduling problem with due date-related objectives.…”
Section: Two-agent Scheduling Problem With the Number Of Tardymentioning
confidence: 78%
“…e literature studies other variants of the two-agent scheduling problem. However, they differ from the problem considered in this paper in terms of either objective function (Wan et al [21]; Mor and Mosheiov [22]) or machine settings (Mor and Mosheiov [23]; Lei [24]; Yu et al [25]). A literature survey by Li et al [26] and Yin et al [27] can be referred to find different variants of the two-agent scheduling problem with due date-related objectives.…”
Section: Two-agent Scheduling Problem With the Number Of Tardymentioning
confidence: 78%
“…Some relevant literatures suggested that the LPT algorithm on addressing makespan minimization problem is quite appropriate. 5,29,30,[31][32][33][34][35] LPT algorithm: Sort all jobs in non-increasing order of their processing times. Each job is subsequently assigned to a machine on which it can be finished as early as possible.…”
Section: Worst-case Ratio Analysismentioning
confidence: 99%
“…Consequently, schedules that minimize the total tardiness lead to high performance, customer satisfaction, and minimum penalty. For more recent development in minimizing total tardiness, readers can refer to [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%